Isolation and Evaluation of Aspergillus Niger : A Fungi Implicated in Infectious Diseases and its application as potential Biofertilizer - Deepa Gautam (Recent Trends in Infectious Diseases, 2023)
In the quest to improve the agronomic effectiveness of Rock Phosphate (RP), a widely available and cost-effective phosphate fertilizer, this study aimed to overcome its limited solubility by isolating fungal strains capable of solubilizing rock phosphate. Soil samples were collected from Garhmukteshwar, Hapur, for the isolation process. Among several isolates, three strains exhibited the highest rock phosphate solubilization within a seven-day timeframe, coinciding with a significant decrease in soil pH. To assess the practical implications of these findings, the bio-fertilizer activity of the identified isolates was evaluated in natural environmental conditions, specifically on Phaseolus vulgaris (Common bean). The experimental results demonstrated a significant positive impact on plant growth when rock phosphate was co-applied with these phosphate solubilizing fungi. This symbiotic interaction between the fungal strains and rock phosphate not only increased nutrient availability for the plants but also showcased the potential to enhance overall soil fertility. These findings contribute valuable insights to sustainable agriculture, emphasizing the potential of leveraging microbial interactions to optimize the performance of widely used fertilizers. The significance of this study goes beyond Garhmukteshwar, offering a promising approach to address the solubility challenges of rock phosphate and enhance its efficacy as a phosphate fertilizer in various agricultural settings. The identified fungal strains represent a novel avenue for the development of bio-fertilizers, contributing to more sustainable and productive agricultural practices.
Keywords: Aspergillus niger; Biofertiliser; Fungus; Isolation; Phosphate solubilizing